Стиль педагогических взаимоотношений будущего учителя английского языка - Байманова, У.Ш.; Бердимуратова, Р.Е. (SCIENCE and SOCIETY, 2020)
The article deals with the pedagogical style of communication of the future English teacher, the peculiarities of interaction and general characteristics of communicative activity. The effectiveness of the words of the teacher in his work with students reflects a deep understanding of his experience in the field of pedagogy, psychology, philology, linguistics, practical experience in teaching students, his intellect and culture of speech.
Keywords: pedagogy; psychology; teacher; speech; philology; linguistics; methods